Letter: combination of biologics in inflammatory bowel diseases. Issue 3 (13th July 2020) - Fumery, Mathurin; Yzet, Clara; Brazier, Franck
Abstract : LINKED CONTENT This article is linked to Yang et al papers. To view these articles, visit https://doi.org/10.1111/apt.15719 and https://doi.org/10.1111/apt.15919 .